THE INFLUENCE OF TSUNAMI RELOCATED HOUSING ON THE CHANGES IN THE ACEH COASTAL MOUNTAIN NATURE AND IMPACT ON ECONOMIC ACTIVITIES OF LOCAL COMMUNITIES - Wulandari, elysa; Zahriah, Zahriah; Fuadi, Zahrul; Sabila, Farisa (Universitas Pendidikan Indonesia, 2020)
Abstract - This paper reveals how the land use change process occurred due to the construction of post-tsunami relocation housing environments, and its impact on the pattern of daily economic activities of local communities in the coastal hilly areas. This study is important along with UU no. 24 Tahun 2007 concerning disaster management that disaster reconstruction activities must take into account the character of the local community and environmental sustainability. The phenomenological approach in this study is by observing the symptoms of the interaction between the artificial environment of the estate settlement, rural environment, and local residents-immigrants and the impact of the system's sustainability in the region. The data such as: 1) pre-tsunami and current land use maps (2020); 2) observation data, regarding daily activities of economic activities in the area; 3) interviews with community leaders to explain the dynamics of local people's economic activities. The analysis method uses a manual interaction diagram system, to read the causality structure which analyzed with â€œlogic of spaceâ€. The results are: a) the location of relocated housing has shifted the location of livestock grazing and agricultural gardens towards hills as well as developing mining business activities C about 0.5-1Km from the housing, which is at risk of natural hazards; b) the housing environment somehow hinders the peopleâ€™s daily freedom of movement and livestock towards the hills. Livestock sometimes cross residential areas and even eat plants in house yards and green open spaces and these disturb the comfort of residential residents. The conclusion is that the pattern of placing the relocated housing environment has created â€œspace in spaceâ€ which changes the pattern of community home-range activities. Suggestions for the sustainability of the economic life of local residents and the comfort of living for newcomers are the need for a strategy to organize an official route of movement to the hills and to make improvements to land for the hills, as well as the obligation to permanently fence off the housing environment. Both things are done with systems approach and synergize the interests of local communities and migrant communities.Â Keywords â€“ relocated housing, vernacular settlements, hilly coastal areas, spatial behavior, Aceh Besar